Do Investors Prefer State-Owned over Other Listed Pharmaceutical Companies During COVID-19? Evidence from Indonesian Stock Exchange - Basuki, Yudha (Universitas Islam Internasional Indonesia, 2022)
This study aims to examine the preference of investors of pharmaceutical companies, including companies that produce herbal medicines, listed in the Indonesian Stock Exchange from 2020 to 2021. By using the descriptive analysis method and reviewing the daily stock prices of Indofarma (INAF), Kimia Farma (KAEF), Kalbe Farma (KLBF), and Sido Muncul (SIDO) in that period, it was found that there were unusual stock prices increases for state-owned pharmaceutical enterprises during those times. However, a similar occurrence did not occur with the other listed pharmaceutical companies, including one herbal medicine manufacturer. In comparing stock price movement trends, the researcher used Microsoft Excel software. The researcher also reviewed the monthly stock closing prices and the news published at that moment. It was found that related events and news existed for every significant increase in stock prices, which might influence investors' perceptions. In addition, the researcher also examined the data to test whether there was a correlation between the number of infected cases and stock prices using the ARCH model estimation. It was found that the relationship between both of them was insignificant. The researcher expects that the findings of this research not only will be a discussion topic in academic groups but also will be a reference for capital market investors and the government as the policyholders and controlling shareholders of these state-owned enterprises. Further studies on listed pharmaceutical companies in the capital markets of other countries are needed to complete the findings in this research, which may find different facts due to different policies in handling the COVID-19 pandemic.